Scrutinizing Problems and Needs of Non-Formal Education Students on English Communication Skills - Wadinlada Thuratham (Journal of Educational Issues, 2024)
To have necessary and ready skills for careers in the 21st century, students should be given awareness of the importance of English, not only in formal but also non-formal and informal education. However, students still lack English abilities, and their English communication skills are still in need of development. Thus, this study aims to analyse the non-formal education students’ problems and needs for improving their English communication skills. The participants in this study are students from the Offices of Non-Formal and Informal Education in the eastern economic corridor (EEC), Thailand. To obtain the data, research instruments, including questionnaire and semi-structured interview were employed in the study. Then, the data were analyzed statistically by using the SPSS program to find percentage, mean and standard deviation, and the content analysis was used to analyze the qualitative data collected from the instruments employed in this study. The findings from this study demonstrated that the students had moderate problems with English communication skills. The students required “conversation in daily life” activities to develop their listening and speaking skills the most and “letter or e-mail” activities to develop their reading and writing abilities the most. Additionally, the results from semi-structured interview, yielded the teachers’ perceptions of the students’ English communication skills in various aspects. As a result, this study would provide pathways for teachers to find effective teaching methods and activities to eliminate the students’ problems and thoroughly fulfil their needs on English communication skills.